Uruguay : Fourth Review Under the Stand-By Arrangement and Requests for Modification of the Arrangement and Waiver of Nonobservance and Applicability of Performance Criteria, and Extension of Repurchase Expectations in the Credit Tranches-Staff Report; Supplementary Information; Press Release on the Executive Board Discussion; Statement by the Executive Director for Uruguay; and Statement by the Authorities of Uruguay. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Uruguay's Fourth Review Under the Stand-By Arrangement and Requests for Modification of the Arrangement. The macroeconomic framework is broadly on track, but progress with structural reform has lagged. With regard to the quantitative performance criteria, there was a small deviation from the target on the combined public sector primary balance. The restructuring of the public banks and the disposal of assets of liquidated banks are taking longer than expected. The authorities have reaffirmed their commitment to the primary surplus targets for 2004 and beyond.